30 % Frequency-Tuning-Range 60 GHz Push-Push VCO in 28 nm Bulk CMOS Technology - Rimmelspacher, Johannes; Weigel, Robert; Hagelauer, Amelie Marietta; Issakov, Vadim (Radio & Wireless Week 2018, 2018)
This paper presents a 60 GHz push-push crosscoupled voltage-controlled oscillator (VCO) in 28 nm bulk CMOS technology. It achieves a continuous frequency tuning range (FTR) of 30% from 52 to 71 GHz in a single sweep. We propose coupling the fundamental harmonic from the VCO core by means of magnetic coupling via a transformer-based resonant tank. This is used instead of directly connecting the output buffers to the oscillation node. The VCO provides a phase noise in the range of -93 to -82 dBc/Hz at 1 MHz offset from carrier across the entire FTR. The measured DC power dissipation including buffers at the fundamental and second harmonic outputs does not exceed 68 mW. The circuit operates from a single supply of 0.9 V. The circuit area excluding pads is 0.15 mm2. Thanks to the achieved very wide continuous FTR, the presented VCO is suitable for FMCW radar applications that require a very fine range resolutio